2007
DOI: 10.1016/j.geb.2006.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Trust and trustworthiness across different age groups

Abstract: We examine the degree of trust and trustworthiness in an experimental trust game with 662 participants from six different age groups, ranging from 8-year-olds to retired persons. Although both trust and trustworthiness have been identified as fundamental pillars for efficient economic interactions, economic research has devoted little attention to measuring their strength in different age groups. In our experiment subjects interact with members of the same age group. We find that trust increases almost linearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
275
5
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 409 publications
(334 citation statements)
references
References 41 publications
35
275
5
5
Order By: Relevance
“…Harbaugh et al (2003), who study 310 subjects aged 7 to 18, find that young children behave more selfishly in dictator games than do older subjects. The same pattern is found for second-mover behavior in trust games -where second movers play basically a dictator game -by Sutter and Kocher (2007). Fehr et al (2008) show in an experiment with 229 children that inequality aversion develops strongly between the ages of 3 and 8.…”
Section: Introductionsupporting
confidence: 62%
“…Harbaugh et al (2003), who study 310 subjects aged 7 to 18, find that young children behave more selfishly in dictator games than do older subjects. The same pattern is found for second-mover behavior in trust games -where second movers play basically a dictator game -by Sutter and Kocher (2007). Fehr et al (2008) show in an experiment with 229 children that inequality aversion develops strongly between the ages of 3 and 8.…”
Section: Introductionsupporting
confidence: 62%
“…They reported that increasing age is associated with higher trust. Sutter and Kocher (2007) examined trust and trustworthiness in different age groups and they reported a linear increase from early childhood to early adulthood. Within the different adult age groups, however, trust remains constant.…”
Section: Discussionmentioning
confidence: 99%
“…Some papers have studied children playing games with a focus on fairness and trustworthiness (distinct from truthfulness) in ultimatum and trust games (10)(11)(12); this literature builds on earlier experimental economics research with children (13)(14)(15). Sally and Hill (16) examined the effects of autism on children's performance in games, with a focus on fairness.…”
Section: Significancementioning
confidence: 99%